2020
DOI: 10.1098/rstb.2019.0612
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus macaques as a tractable physiological model of human ageing

Abstract: Research in the basic biology of ageing is increasingly identifying mechanisms and modifiers of ageing in short-lived organisms such as worms and mice. The ultimate goal of such work is to improve human health, particularly in the growing segment of the population surviving into old age. Thus far, few interventions have robustly transcended species boundaries in the laboratory, suggesting that changes in approach are needed to avoid costly failures in translational human research. In this review, we discuss bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 78 publications
2
85
0
Order By: Relevance
“…For example, physiological dysregulation does not appear to vary systematically between men and women, a finding confirmed here in a small-scale horticultural population [88]. As in human studies, rates of DNA methylation showed minimal sex differences in chimpanzees and rhesus macaques [64,89].…”
Section: (D) Sex Differences In Ageingsupporting
confidence: 75%
See 4 more Smart Citations
“…For example, physiological dysregulation does not appear to vary systematically between men and women, a finding confirmed here in a small-scale horticultural population [88]. As in human studies, rates of DNA methylation showed minimal sex differences in chimpanzees and rhesus macaques [64,89].…”
Section: (D) Sex Differences In Ageingsupporting
confidence: 75%
“…For example, despite considerable diversity in lifespan, primates exhibit broad similarities in the patterning of mortality that distinguish them from other species [55,56]. Primates share physiological similarities with humans that make them highly relevant models for reproductive ageing, metabolic diseases, musculoskeletal ageing, immune function, cardiovascular disease and cognitive decline [57][58][59][60][61][62][63][64]. Finally, given the overall similarities, the variation among primates is specifically informative.…”
Section: Challenges and Benefits Of Comparative Ageing Research On Nomentioning
confidence: 99%
See 3 more Smart Citations